Aplikasi Mobile Untuk Monitoring Tanaman Hidroponik Kangkung Berbasis Thingspeak dan Firebase - Atmaja, Fakhri Tri; Muhammad Fachrie (Jurnal Ilmu Komputer dan Agri-Informatika, 2023)
One of the hindrances to agricultural growth in Indonesia is the diminishing agricultural land. Hydroponics is a potential solution for the challenges faced by farmers with limited land resources, since it enables cultivation to be conducted in water-based environments, both vertically and horizontally. Gubuk Mbah Bayan is an individual engaged in the cultivation of hydroponic plants. Gubuk Mbah Bayan continues to employ a manual monitoring technique, requiring farmers to physically visit the field in order to assess the state of the agricultural environment. The objective of this study is to enhance an automated monitoring system designed for monitoring hydroponic plant culture conditions. The system utilizes temperature, total dissolved solid (TDS), and pH data. The proposed system adopts the Internet of Things (IoT) paradigm, connecting Arduino microcontroller with digital sensors. This research encompasses five distinct steps, which include problem identification, system architecture design, program implementation, integration, and testing. The outcome of this research is the development of a hydroponic plant cultivation monitoring system, conveniently accessible through a mobile application. This technology enables farmers to remotely and instantly monitor the hydroponic environment. The testing employed in this study is the system usability scale (SUS) approach. The hydroponic monitoring application demonstrates satisfactory performance, user-friendliness, and utility in assisting farmers with monitoring the hydroponic environment.